Nexus of minerals-technology complexity and fossil fuels with carbon dioxide emission: Emerging Asian economies based on product complexity index. (1st November 2022) - Baz, Khan; Xu, Deyi; Ali, Hashmat; Khan, Uzma; Cheng, Jinhua; Abbas, Khizar; Ali, Imad
Abstract: Increasing concern regarding environmental degradation has led researchers to examine the potential of advanced technology in climate change. In this regard, complexity in green technology is considered in the study, which has not been acknowledged in earlier studies. Combined, renewable energy and technological advancement may overcome environmental issues significantly. Therefore, the study examines the impact of technological complexity, fossil fuel, renewable energy, and complex minerals on environmental quality within sustainable economic growth for the period of 1995–2018. Econometric methods are employed to solve the problems of cross-sectional dependence and heterogeneity in comprised variables. Co-integration was confirmed by employing the Westerlund test; a long-run relationship is shown by dynamic and fully modified ordinary least square regressions. In the long run, fossil fuel and technological complexity degrade the environmental quality, while complex minerals improve the environmental quality. Moreover, bidirectional causality between technological complexity and carbon dioxide emission, while one-way causality also noted running from fossil fuel to carbon emission used panel vector auto-regressive test. Based on the findings, the importance of understanding technologies' complexity along with energy mix in firms and regions within global value chains for accomplishing policy goals is important. Additionally, the inability of clean technologies equipment and critical minerals supply at the required market expansion rates are key problems for minimizing the region's carbon emissions for policy. Graphical abstract: Image 1 Highlights: Impact of critical minerals on environmental quality. Examine the role of technological complexity in CO2 . Technological advancement, environmental quality, and mineral resources nexus. Minerals-batteries are currently using in modern technologies as alternate power.